1991
DOI: 10.1128/jb.173.14.4417-4423.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence that genes fdhD and fdhE do not control synthesis of formate dehydrogenase-N in Escherichia coli K-12

Abstract: Enterobacteria synthesize two formate dehydrogenases, formate dehydrogenase-N (encoded byfdnGHI) and formate dehydrogenase H (encoded by fdhF). Previous work has identified two rha-linked Salmonella typhimurium genes, fdnB and fdnC, which are required primarily for formate dehydrogenase-N activity. Analogous mutants, termed fdhD and fdhE, have been isolated in Escherichia coli. We used gene fusions betweenfdnG, the structural gene for the large subunit of formate dehydrogenase-N, and lacZ, the structural gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This observation correlates with the failure to detect any FDH-N polypeptides in fdhE mutants by rocket immunoelectrophoresis (30). Our results show clearly that neither fdhD nor fdhE lesions affect fdo expression (Table 5), in parallel with previous work from Stewart and coworkers giving evidence that fdhD and fdhE do not control transcription of fdn (48). Taken together, these data support the idea that the FdhD and FdhE proteins act at the posttranslational level to ensure the correct processing or assembly of both respiratory FDH isoenzymes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This observation correlates with the failure to detect any FDH-N polypeptides in fdhE mutants by rocket immunoelectrophoresis (30). Our results show clearly that neither fdhD nor fdhE lesions affect fdo expression (Table 5), in parallel with previous work from Stewart and coworkers giving evidence that fdhD and fdhE do not control transcription of fdn (48). Taken together, these data support the idea that the FdhD and FdhE proteins act at the posttranslational level to ensure the correct processing or assembly of both respiratory FDH isoenzymes.…”
Section: Discussionsupporting
confidence: 80%
“…The fdhD and fdhE genes encode accessory proteins which are required for the formation of both respiratory FDH isoenzymes in an active form (36,42,48) while the selAB operon has been shown to be involved in selenium incorporation as a selenocysteine to produce the three FDHs in a functional state (10,41). Whatever the mutation tested (Table 5, rows 8, 9, 12, and 13), the pattern of expression of the fdo-uidA fusion did not show any significant change.…”
Section: Resultsmentioning
confidence: 94%
“…In addition to TusA and IscU, large-scale interactome studies identified FdhD as a binding partner of IscS (7,8). FdhD has been shown to be required for the activity of formate dehydrogenases (FDHs) 2 in E. coli through an unknown mechanism (9,10). E. coli synthesizes three FDHs that decompose formate to carbon dioxide and protons.…”
mentioning
confidence: 99%
“…In E. coli, FdhD was found to be essential for activity of the two respiratory FDHs FDH-N and FDH-O as well as for the fermentative FDH-H (Abaibou et al, 1995;Schlindwein et al, 1990;Stewart et al, 1991). Recently, FdhD from E. coli was shown to interact with IscS, one of the three E. coli L-cysteine desulfurases (ThomĂ© et al, 2012).…”
Section: Discussionmentioning
confidence: 99%